Pengaruh Suhu Air Penyiraman Terhadap Pertumbuhan Bibit Cabai (Capsicum annum L.) - Muhammad Hatta (Fakultas Pertanian, Universitas Syiah Kuala, 2006)
Effects of Watering Temperature on Seedling Growth of Chili (Capsicum annum L.)ABSTRACT. Researches of temperature effect on plant have yet to provide obvious results of how leaf temperature and media temperature differs plant growth. The research of objectives are to study effects of water temperature irrigated to media and water temperature sprayed to the leaves on chili seedling growth. Completely randomized block design was used in the research. The factor studied were water temperature for watering media and water temperature for spraying seedling leaves. The result showed that water temperature for spraying seedling leaves significantly affected all variables observed, including seedling height, seedling diameter, leaf size, wet weight of seedling, wet weight of the roots, dried weigh of seedling, and dried weigh of the roots. Water temperature for watering media did not significantly affect all variables observed. There were significant interactions between water temperature for watering media and water temperature for spraying seedling leaves on seedling diameter and leaf size. Water temperature of 120C for watering media in combination with normal water temperature for spraying seedling leaves was the best treatment combination, while water temperature of 120C for watering media in combination with 120C water temperature for spraying seedling leaves was the worst treatment.